Suppression of creep-regime dynamics in epitaxial ferroelectric BiFeO(3) films - Shin, Y. J. (Sci Rep, 2015)
Switching dynamics of ferroelectric materials are governed by the response of domain walls to applied electric field. In epitaxial ferroelectric films, thermally-activated ‘creep’ motion plays a significant role in domain wall dynamics, and accordingly, detailed understanding of the system’s switching properties requires that this creep motion be taken into account. Despite this importance, few studies have investigated creep motion in ferroelectric films under ac-driven force. Here, we explore ac hysteretic dynamics in epitaxial BiFeO(3) thin films, through ferroelectric hysteresis measurements, and stroboscopic piezoresponse force microscopy. We reveal that identically-fabricated BiFeO(3) films on SrRuO(3) or La(0.67)Sr(0.33)MnO(3) bottom electrodes exhibit markedly different switching behaviour, with BiFeO(3)/SrRuO(3) presenting essentially creep-free dynamics. This unprecedented result arises from the distinctive spatial inhomogeneities of the internal fields, these being influenced by the bottom electrode’s surface morphology. Our findings further highlight the importance of controlling interface and defect characteristics, to engineer ferroelectric devices with optimised performance.